Housekeeping Management - Casado Matt A (Wiley, 2012)
This book uniquely applies its theoretical content through presentation of practical case studies. Introduction to housekeeping Management, The Housekeeping Department in Lodging Operations, The Executive Housekeeper as Department Manager, Design of the housekeeping Department.